Pengaruh Pajak, Tunneling Incentive, Mekanisme Bonus, dan Profitabilitas terhadap Transfer Pricing - Sudarmanto, Eko; Aulia, Triana Zuhrotun; Putri, Rumanintya Lisaria (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The purpose of this study is to determine the impact of taxation, tunneling incentives, bonus mechanisms, and profitability on the transfer pricing of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study period used was 5 years, 2017-2021. The subject of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. The sampling technique is a targeted sampling technique. Based on certain criteria, 34 companies were identified. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method adopted is panel data regression analysis. The results show that bonuses and profit mechanisms have an impact on transfer pricing. At the same time, tax and tunnel construction incentives have no impact on transfer pricing.